2009
DOI: 10.1147/jrd.2009.5429058
|View full text |Cite
|
Sign up to set email alerts
|

The Reservoir model and architecture for open federated cloud computing

Abstract: The emerging cloud-computing paradigm is rapidly gaining momentum as an alternative to traditional IT (information technology). However, contemporary cloud-computing offerings are primarily targeted for Web 2.0-style applications. Only recently have they begun to address the requirements of enterprise solutions, such as support for infrastructure service-level agreements. To address the challenges and deficiencies in the current state of the art, we propose a modular, extensible cloud architecture with intrins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
305
0
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 642 publications
(313 citation statements)
references
References 21 publications
0
305
0
8
Order By: Relevance
“…With respect to our previous work [11] and the Reservoir project [13] [18] [28] [39], the distinguished dif-ferences of our ESP model are three-fold. First, in our model, developing a new service management layer (TRE) for another different workload is lightweight, since many common functions, e.g., the monitors, which are responsible for monitoring and reporting resources status, are required by each service management layer, have been implemented in the common service management framework (CSF).…”
Section: The Enhanced Scientific Public Cloud (Esp) Modelmentioning
confidence: 93%
See 1 more Smart Citation
“…With respect to our previous work [11] and the Reservoir project [13] [18] [28] [39], the distinguished dif-ferences of our ESP model are three-fold. First, in our model, developing a new service management layer (TRE) for another different workload is lightweight, since many common functions, e.g., the monitors, which are responsible for monitoring and reporting resources status, are required by each service management layer, have been implemented in the common service management framework (CSF).…”
Section: The Enhanced Scientific Public Cloud (Esp) Modelmentioning
confidence: 93%
“…C Loud computing has attracted a lot of attention in the last few years [2] [4] [13] [20] [28]. From the perspective of resource providers, such as Amazon and Google Apps, cloud computing introduces a new computing paradigm: infrastructure-as-a-service (IaaS) or platform-as-a-service (PaaS).…”
Section: Introductionmentioning
confidence: 99%
“…Rochwerger et al [2] identified a number of inherent deficiencies in the current cloud computing systems, such as, limited scalability of single provider of clouds, lack of interoperability among the cloud providers and lack of built-in business service management support. Therefore, they proposed an architecture called 'RESERVOIR' to address the needs of enterprise-grade solutions, such as support for infrastructure level SLAs.…”
Section: Motivational Scenariomentioning
confidence: 99%
“…His prediction has come into reality in the form of cloud computing after a century. Cloud computing is the latest incarnation of a general purpose public computing utility [2].…”
Section: Introductionmentioning
confidence: 99%
“…If you are a cloud computing user, you will be able to first use its extraordinary stronger processing powerbecause your system might not have the necessary processing power. Second, you will be able to perform these very heavy operations concurrently with several of your friends and observe each other's work output on the project instantaneously [5]. Among its other potentials is that up to now you had to take advantage of your systems processing resources individually and once in a while you were forced to up to date your system hard and software to be able to both access the most current software versions and also had need for hard ware power for supporting your software.…”
Section: Introductionmentioning
confidence: 99%